Can ischemic preconditioning improve CMJ performance in young elite basketball players? A pilot study. - Ricart Luna, B.; Cerrillo, J.; Rodrigo-Mallorca, D.; Alonso-Aubin, D. A.; Chulvi-Medrano, I. (Journal of Physical Education and Sport, 2022)
Ischaemic preconditioning (IP) is a non-invasive method based on brief periods of ischaemia followed by periods of blood reperfusion by means of a tourniquet placed on the proximal part of the limb to be trained. In recent years, its effects on post-activation performance enhancement (PAPE) have been investigated as a pre-workout potentiation strategy with high demands on strength and neuromuscular power. The objective of the present study was to record the acute effects induced by an ischemic preconditioning (IPC) protocol on jumping ability in elite basketball players. 22 basketball players (17.31 (1.35) years old; 195 (0.05) cm; 86.36 (6.71) kilograms; 22.60 (1.73) kg/m2) from a professional club were recruited. After a familiarization phase with IPC subjects were involved in the experimental phase (48 h after). Following 5 minutes cycling warm-up a pressurized cuff (250 mmHg) was applied in the inguinal region using a protocol of 4 sets of 5 minutes with IPC interspersed 5 minutes of reperfusion (0 mmHg). 5 countermovement jumps on platform force were performed before and after (10minutes after) IPC protocol. IPC intervention showed a significant (p<0.05) increased acute jump performance in the mean PRE 31,02 (4.13) cm / 1026.90 (101.28) watts vs POST 32.97 (3.60) cm / 1058,55 (92.72) watts and in the best record PRE 32.55 (4.05) cm /1052.57 (100.83) watts VS POST 34.66 (4.10) cm / 1080.42 (103.11) watts on CMJ jump. The results showed a small size effect. IPC as warm-up in young elite basketball players may induce post-activation performance enhancement in power increasing CMJ outcome.